Making decisions that matter : how people face important life choices - Galotti, Kathleen M., 1957- (L. Erlbaum, 2002)
This work aims to describe ongoing research that examines real people making real decisions, and compares it with theoretical predictions to provide readers with "food for thought" when it comes to their own decision making and point out issues that await further research.